Association of Psychological Stress and Mood in Ankle Injuries among Basketball Players during Conditional Movement Control Order - Puah, Jia Qi; Gaspar, Edwin; Nur Fadhilah, Faiz; Viswanath, Sundar; Vinodhkumar, Ramalingam (INTI International University, 2021)
Background: Ankle injuries in basketball are very common and have been increasing drastically over the past several decades. Based on studies, it believed that psychological effects play an important role in affecting sports injuries. In addition, during the conditional movement control order (CMCO), the athletes are forced to train at a reduced volume and intensity, which impairs performance and may lead to injury. Objective: This study aims to find the association between psychological stress and mood in ankle injuries among basketball players during CMCO. Methodology: An online questionnaire distributed via Google form links to basketball players who were involved in individual practice in Selangor, Malaysia. The collected data then analyzed using IBM SPSS Statistics 25. The Spearman correlation coefficient used to analyze the association between the Perceived Stress Scale (PSS), Profile of Mood State-Short form (POMS-SF) and the Foot Ankle Disability Index (FADI). Results: Prevalence of ankle injuries among basketball players during CMCO was reported at 84.4%. Among the 151 participants, 7.9% had low perceived stress and 92.1% had moderate perceived stress. The association between FADI and PSS did not reach statistical significance, while the association between POMS-SF and FADI was significant at 0.01 and 0.05 level. Conclusion: According to the findings, basketball players are more likely to get ankle injuries, and most players are in a negative mood during CMCO, which affects their regular training and may increase the injury rate.